Demographic development of the CIS countries: the case of Uzbekistan - Salimov Sherzod Yunusovich; Samadov Khurshid Samadovich (Proceedings of The ICECRS, 2019)
This article gives a specified place of population of the Republic ofUzbekistan among the CIS countries. A dynamics of the population of theRepublic of Uzbekistan for 1991-2015 was obtained. Also, an analysis of thestructure of the population according to number, age and distribution wascarried out.